Doxing sebagai Ancaman Hak Privasi: Analisis Normatif atas Disharmoni UU ITE dan UU PDP - Krisliana Firsty Mutiarani; Ni Komang Sutrisni; I Nengah Susrama; Anak Agung Adi Lestari (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2026)
Doxing, as a form of cybercrime, has become a serious threat to individual privacy rights in the digital era. The practice of disclosing personal data without consent not only violates human dignity but also infringes upon the constitutional right to security guaranteed under Article 28G paragraph (1) of the 1945 Indonesian Constitution. In Indonesia, doxing is regulated under the Electronic Information and Transactions Law (ITE Law) and the Personal Data Protection Law (PDP Law). However, these two regulations emphasize different aspects: the ITE Law focuses on cybercrime’s technical dimension, while the PDP Law emphasizes the protection of personal data subjects’ rights. This difference creates normative disharmony in terms of definition, offense characteristics, and sentencing disparity, which results in legal uncertainty and weak protection for doxing victims. Using normative legal research methods, this study examines the disharmony between the ITE Law and PDP Law and its implications for privacy protection. The findings show that without regulatory harmonization, the PDP Law as lex specialis cannot optimally protect victims. Therefore, harmonization of regulations, strengthening of the personal data supervisory authority, and enhancing the capacity of law enforcement officers are urgently needed to ensure legal certainty and effective privacy protection in Indonesia.